2009
DOI: 10.1016/j.jcis.2008.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of PDMS membrane and microcantilever by a water droplet: Comparison between Mooney–Rivlin and linear elastic constitutive models

Abstract: In this paper, we studied the role of vertical component of surface tension of a water droplet on the deformation of membranes and microcantilevers (MCLs) widely used in lab-on-a-chip and micro- and nano-electromechanical system (MEMS/NEMS). Firstly, a membrane made of a rubber-like material, poly(dimethylsiloxane) (PDMS), was considered. The deformation was investigated using the Mooney-Rivlin (MR) model and the linear elastic constitutive relation, respectively. By comparison between the numerical solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 34 publications
(40 reference statements)
0
59
0
Order By: Relevance
“…Apart from investigations of such a problem either theoretically or experimentally, some numerical studies have also been reported [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from investigations of such a problem either theoretically or experimentally, some numerical studies have also been reported [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…As already addressed, the mechanical properties of PDMS are highly dependent on the degree of cross-linking [10,13,15,16]. The sample preparation in [13] provided curing for 15 min at 150°C in an oven, whereas our replication process (optimised for successful separation of the undercut structures) works with 30 min on a hotplate at 80°C.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its mechanical properties [13], it offers an excellent replication accuracy and is thus widely used for soft lithography [11]. However, the material properties strongly depend on the degree of cross-linking obtained during curing so that its mechanical properties may vary by up to two orders of magnitude [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The PDMS standard had a Young's modulus of 2.1 MPa and a Poisson's ratio of 0.499 [28]. The cylindrical PDMS block was 60 mm in diameter and 10 mm in height (see Fig.…”
Section: Experiments Proceduresmentioning
confidence: 99%